"Women's empowerment through seed improvement and seed governance: Evidence from participatory barley breeding in pre-war Syria". (1st June 2017) - Galiè, Alessandra; Jiggins, Janice; Struik, Paul C.; Grando, Stefania; Ceccarelli, Salvatore
Highlights: Gender-responsive participatory plant breeding can empower women farmers. Gender-blind international seed legislation and customary rules undermine empowerment. Empowerment is a non-linear process of self, intra-household and public negotiations. Gender affects what and how seed activities are done and thereby also variety preferences. Abstract: Approaches to food security primarily focus on technological solutions, seeking to produce more food, preferably with fewer resources. It has been argued that access to food involves issues of resource distribution and social marginalization. Governance is seen as one of the keys to redressing the institutional inequity that affects resource distribution. Rural women's empowerment is seen as a means to reduce social marginalization and to hasten progress towards hunger eradication and gender equitable institutions. Building on the empirical findings of a six-year study (2006–2011) undertaken in the context of a participatory barley breeding (PBB) programme in pre-war Syria, this paper establishes the links between women's empowerment, seed improvement through PPB and seed governance vis-à-vis household food security. The study shows how the programme enhanced the empowerment of the respondent women and how gender-blind seed governance regimes at national and international levels restricted the empowerment of these women ultimately affecting the pillars of food security. We discuss some of the challenges encountered by the study in conceptualizing and operationalizing gender analysis to enhance women's empowerment. The article further discusses the interplay of processes to both discipline gender norms and provides transformational opportunities towards gender equity created by public spaces such as the PBB programme. The article contributes to current discussions on the effective pathways to develop smallholder agriculture, enhance gender equity and enhance food security and rural livelihoods in the dry areas of the temperate world.